Whose feminism is it anyway? The unspoken racism of the trans inclusion debate. Issue 4 (July 2020) - Koyama, Emi
This essay was first published on Emi Koyama's websiteeminism.org in 2000. Koyama examines how constructs of universal womanhood have operated to exclude many from feminist spaces. Much of the language surrounding trans identities and bodies has changed in the 20 years since its authorship. Yet, the central tensions, illustrated through a critical account of the Michigan Womyn's Music Festival's trans-exclusion policy, remain. Koyama's powerful argument that 'no-penis' policies are inherently racist and classist continues to offer an important challenge to white feminists, be they trans or cis.